The influence of Rooibos (Aspalathus linearis) on adrenal steroidogenic P450 enzymes - Perold, Helene (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Biochemistry))--University of Stellenbosch, 2009.